The Effect Of Temperature and Time on Hydrolisis of Palm Oil Empty Fruit Bunch and Its Enzymatically Biodegradation for Xylose Production - Wisnu Adi Yulianto; Dewa Made Krismanto Panji (Agroindustrial Journal, 2017)
The acid hydrolysis and the heating of lignocellulosic waste from palm oil mills have caused irreversible damage to the natural environment and can create inhibitor compounds on hydrolysis, making the waste improper for fermentation media. In this study, an environmentally save hydrolysis was tested by heating it under high temperature which followed by enzymatic degradation. The objective of the present study was to determine the optimal reaction temperature and reaction time of hydrolysis for the production of xylose. Under the temperatures of 128 and 200°C with reactions time of 30, 45, and 60 min, the best result of hydrolysates were taken. Its hemicellulose, cellulose, lignin, water content (raw material), residual hemicellulose, reducing sugars, water content (hydrolysate) and xylose were analyzed. The results showed that the higher the temperature had resulted in the more reduction of sugar hydrolysis and the hemicellulose in the solid residue was slightly removed. Hydrolysis at the temperature of 200°C for 45 min had indicated a reduction of sugar yield of 17.71% (db). Biodegradation in enzymatic hydrolysis of xylose had increased by 113.79% at 24 -1.24 g xylose / 100 ml.